Synthesis and transfer of galactolipids in the chloroplast envelope membranes of Arabidopsis thaliana - Kelly, Amélie A. (Proc Natl Acad Sci U S A, 2016)
Galactolipids [monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG)] are the hallmark lipids of photosynthetic membranes. The galactolipid synthases MGD1 and DGD1 catalyze consecutive galactosyltransfer reactions but localize to the inner and outer chloroplast envelopes, respectively, necessitating intermembrane lipid transfer. Here we show that the N-terminal sequence of DGD1 (NDGD1) is required for galactolipid transfer between the envelopes. Different diglycosyllipid synthases (DGD1, DGD2, and Chloroflexus glucosyltransferase) were introduced into the dgd1-1 mutant of Arabidopsis in fusion with N-terminal extensions (NDGD1 and NDGD2) targeting to the outer envelope. Reconstruction of DGDG synthesis in the outer envelope membrane was observed only with diglycosyllipid synthase fusion proteins carrying NDGD1, indicating that NDGD1 enables galactolipid translocation between envelopes. NDGD1 binds to phosphatidic acid (PA) in membranes and mediates PA-dependent membrane fusion in vitro. These findings provide a mechanism for the sorting and selective channeling of lipid precursors between the galactolipid pools of the two envelope membranes.